Tinjauan Yuridis Terhadap Penerapan Deportasi Warga Negara Asing di Wilayah Indonesia - Aryuni Fitri Djaafara; Jean Claudia; Valencia Prasetyo Ningrum (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The rapid development of transportation has led to an increase in the number of people moving between countries, so that Indonesia has to control the immigration process more. A sovereign country has the right to accept, refuse or repatriate foreign nationals who enter its territory. However, this does not mean that the state can arbitrarily repatriate foreigners by means of deportation. This research is intended to provide a juridical review of the implementation of the deportation of foreign nationals in Indonesian territory. The writing method used is the library study method, namely by researching in the form of manuscripts, journals, and articles. Foreigners who have committed immigration violations in Indonesian territory are still people who have their human rights. Although deportation is not the only law that applies, deportation is often a shortcut for foreigners in Indonesia. For that it will be a violation of human rights that can be tried and heard in court. To overcome these problems, immigration law enforcers play an important role in protecting the human rights of foreigners with legal procedures that comply with the law, human rights and the code of ethics as immigration officers